2019
DOI: 10.3390/w11050951
|View full text |Cite
|
Sign up to set email alerts
|

Outlier Detection and Smoothing Process for Water Level Data Measured by Ultrasonic Sensor in Stream Flows

Abstract: Water level data sets acquired by ultrasonic sensors in stream-scale channels exhibit relatively large numbers of outliers that are off the measurement range between the ultrasonic sensor and water surface, as well as data dispersion of approximately 2 cm due to random errors such as water waves. Therefore, this study develops a data processing algorithm for outlier removal and smoothing for water level data measured by ultrasonic sensors to consider these characteristics. The outlier removal process includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…Missing values in the data were estimated by linear interpolation. Outliers were checked using the modified z-score method [ 42 , 43 , 44 ] and removed from the data. This method is expressed by the following equation: where is the modified z-score, and and are the i th ordinate and median of a feature vector, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Missing values in the data were estimated by linear interpolation. Outliers were checked using the modified z-score method [ 42 , 43 , 44 ] and removed from the data. This method is expressed by the following equation: where is the modified z-score, and and are the i th ordinate and median of a feature vector, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A recent work has also shown that water level measurements from an ultrasonic sensor can be improved if an algorithm scans the time-series data for removing outliers and random errors such as the ones caused by small waves [ 36 ]. From the experience with the Pikrodafni urban stream in the case study of our paper and the relatively short time-series that is already available though, no significant outliers are observed, while errors due to random factors are not expected to be high.…”
Section: Discussionmentioning
confidence: 99%
“…From the experience with the Pikrodafni urban stream in the case study of our paper and the relatively short time-series that is already available though, no significant outliers are observed, while errors due to random factors are not expected to be high. However, such an automatic algorithmic process for smoothing the data [ 36 ] may exclude the majority of abnormal values in the future when longer ultrasonic time-series data are expected.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor used in this study is an ultrasonic sensor. Ultrasonic sensors work using a trigger and echo system to determine the distance from the center of the signal transmitter to the object being measured [1][2] [3]. To process sensor data from a flood detection system requires a microcontroller such as an ATMEGA238 microcontroller.…”
Section: Literature Surveymentioning
confidence: 99%